The Effect of Employee Benefit Liabilities and Earnings Management on Tax Avoidance Moderated by Firm Size - Susanty, Caroline Adriani; Yuniarwati (Research Horizon, 2025)
Tax avoidance remains a critical issue affecting government revenue and market fairness. This study aims to examine the effects of employee benefit liabilities and firm size on earnings management on LQ45 companies listed on the Indonesia Stock Exchange. This study analyzes 26 companies selected through purposive sampling and yields 78 firm-year observations over the period 2022–2024. Data are analyzed using panel-based moderated regression analysis after meeting the classical assumption test. The results indicate that employee benefit liabilities have a negative effect on tax avoidance. Earnings management significantly affects accounting-based tax avoidance but does not significantly affect cash-based tax avoidance. Firm size is positively associated with tax compliance and significantly moderates the relationship between employee benefit liabilities and tax avoidance. Large firms with substantial employee benefit liabilities exhibit lower levels of tax avoidance. These findings contribute to a deeper understanding of tax behavior among large and liquid firms in the Indonesian capital market and offer implications for managers, regulators, and policymakers.